Efektivitas Kombinasi Pijat Oksitosin dan Musik Klasik terhadap Peningkatan Produksi ASI pada Ibu Nifas Pasca Persalinan di Klinik Kartika Jaya - Tania, Tania; Ariestantia, Dwi Riyan (Lembaga Teewan Journal Solutions, 2026)
Breast milk is the best source of nutrition for infants as it contains complete nutrients and plays an important role in supporting infant growth and development. One of the common problems experienced by postpartum mothers is insufficient breast milk production, which may affect the success of exclusive breastfeeding. Non-pharmacological methods that can be used to increase breast milk production include oxytocin massage and classical music therapy. This study aimed to determine the effectiveness of oxytocin massage combined with classical music on increasing breast milk production among postpartum mothers 7–40 days after delivery at Kartika Jaya Clinic, Samarinda City, in 2026. This study employed a quasi-experimental design with a pretest-posttest control group approach. The sample consisted of 30 respondents, including 15 respondents in the intervention group and 15 respondents in the control group selected through purposive sampling. The intervention group received oxytocin massage combined with classical music, while the control group received routine postpartum care according to standard procedures. Data were analyzed using the Wilcoxon and Mann-Whitney tests with a significance level of α = 0.05. The results showed an increase in breast milk production in the intervention group after receiving oxytocin massage combined with classical music. Statistical analysis demonstrated a p-value < 0.05, indicating that the combination of oxytocin massage and classical music had a significant effect on increasing breast milk production among postpartum mothers 7–40 days after delivery. The combination of oxytocin massage and classical music is an effective non-pharmacological method for increasing breast milk production and supporting the success of exclusive breastfeeding among postpartum mothers.